2016
DOI: 10.1021/acs.est.6b04325
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics of Polar Chemicals in Zebrafish Embryo (Danio rerio): Influence of Physicochemical Properties and of Biological Processes

Abstract: The time-resolved uptake of 17 nonionic and ionic polar compounds (logD ≤ 2) with a diversity of functional groups into zebrafish embryos (ZFE) was studied over 96 h of exposure. Among them were pharmaceuticals, pesticides and plant active ingredients. Uptake rates for the diffusion controlled passive uptake through the ZFE membrane ranged from 0.02 to 24 h(-1) for the nonionic compounds and were slower for ionic compounds (<0.008-0.08 h(-1)). The study compounds did not enrich much in the ZFE (median bioconce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
83
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 49 publications
(92 reference statements)
10
83
0
2
Order By: Relevance
“…At 72 hpf, in vitro activity of some cytochrome P450s was also observed in zebrafish embryos Verbueken et al 2017). A similar decreasing pattern of internal doses, after a maximum of approximately 24 hpf, was also observed after aquatic exposure to benzocaine, phenacetin, metribuzin (Brox et al 2016), and benz[a]anthracene (Kuhnert et al 2013). In both studies, metabolites of the respective parent compounds were also detected, which supports the hypothesis of biotransformation.…”
Section: Micro-injection Versus Aquatic Exposure: Compound Accumulatisupporting
confidence: 73%
“…At 72 hpf, in vitro activity of some cytochrome P450s was also observed in zebrafish embryos Verbueken et al 2017). A similar decreasing pattern of internal doses, after a maximum of approximately 24 hpf, was also observed after aquatic exposure to benzocaine, phenacetin, metribuzin (Brox et al 2016), and benz[a]anthracene (Kuhnert et al 2013). In both studies, metabolites of the respective parent compounds were also detected, which supports the hypothesis of biotransformation.…”
Section: Micro-injection Versus Aquatic Exposure: Compound Accumulatisupporting
confidence: 73%
“…Uptake of select pharmaceuticals [27,40], perfluorooctanesulfonic acid [41], and polycyclic aromatic hydrocarbons (PAHs) [34,42] has been examined in embryonic stages of zebrafish. For example, there are fewer than 10 previous studies on the uptake of chemicals across embryo-larval stages of fish, and of these, the majority of work has been conducted with either eleutheroembryo or larval stages.…”
Section: Resultsmentioning
confidence: 99%
“…Although some mammalian homologs have been identified, functional conservation has not yet been established for most CYPs [53] across common fish models. For example, investigations of clofibric acid biotransformation [55], and a suite of other polar compounds [40], by developing zebrafish identified the presence of transformation products. For example, investigations of clofibric acid biotransformation [55], and a suite of other polar compounds [40], by developing zebrafish identified the presence of transformation products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an in vitro approach based on the use of sub-cellular microsomal fractions and of specific probe substrates, Verbueken et al [25] concluded that the capacity of intrinsic biotransformation in zebrafish embryos appears to be lacking during a major part of organogenesis, at least concerning key phase I activities. Notwithstanding, recent in vivo studies demonstrated that biotransformation of some compounds can start very early, indicating that some phase I and phase II enzymes are already functional at early life-stages [26,27]. We previously demonstrated that the metabolic capacities expressed in zebrafish hepatic cellular models are close to that of metabolically competent hepatic human cell lines (HepaRG), at least for BPS and BP2 [8].…”
Section: Introductionmentioning
confidence: 99%